18F-FDG-PET/MRI in lymphoma patients - Ferdová, Eva; Ferda, Jiří; Baxa, Jan (European journal of radiology, 2017)
The introduction of hybrid PET/MRI imaging using integrated systems into clinical practice has opened up the possibility of reducing the radiation dose from hybrid imaging by eliminating the contribution from computed tomography. Studies comparing the possibilities of PET/CT and PET/MRI imaging demonstrated it is possible to use the advantages of the high contrast resolution of magnetic resonance for soft tissue and bone marrow along with PET records in a quality comparable to PET/CT imaging. The significant feature for PET imaging in Hodgkińs lymphoma is that it is a tissue with high levels of radiopharmaceutical accumulation, which decreases proportionally after successful therapeutic effect, the effect of therapy is assessed using Deauville score system on interim examinations. While the efficacy of prognosis determined using the Deauville scale in HL is widely accepted, it turns out that in DLBCL, the prognostic value of PET imaging is bound to the evaluation of subtypes. PET/MRI scanning can be used to evaluate a relapse if follicular lymphoma has already been treated, or to confirm transformation into more aggressive forms. In children and adults with Burkitt's lymphoma, negative findings after induction therapy have a high negative predictive value for relapse prognosis.
Keywords: PET/MRI; Fluorodeoxyglucose; Multimodal Imaging; Deauville score; Humans; Lymphoma; Fluorodeoxyglucose F18; Female; magnetická rezonanční tomografie; multimodální zobrazování; Positron-Emission Tomography; ženské pohlaví; lymfom; Magnetic Resonance Imaging; Adult; radiofarmaka; Hybrid imaging; fluorodeoxyglukosa F18; pozitronová emisní tomografie; dospělí; dítě; lidé; Radiopharmaceuticals; Child